Things Fall Apart: The Dynamics of Brand Audience Dissipation - Parmentier, Marie-Agnès; Fischer, Eileen (Journal of Consumer Research, 2015)
Much prior work illuminates how fans of a brand can contribute to the value enjoyed by other members of its audience, but little is known about any processes by which fans contribute to the dissipation of that audience. Using longitudinal data on America's Next Top Model, a serial brand, and conceptualizing brands as assemblages of heterogeneous components, this article examines how fans can contribute to the destabilization of a brand's identity and fuel the dissipation of audiences of which they have been members. This work suggests that explanations focusing on satiation, psychology, or semiotics are inadequate to account for dissipation in the audience for serial brands. Moreover, the perspective advanced here highlights how fans can create doppelgänger brand images and contribute to the co-destruction of serial brands they have avidly followed.